PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER (NHT) UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK AGRIBISNIS TANAMAN PANGAN DAN HORTIKULTURA SMK NEGERI 2 SOPPENG - Nurmila, Nurmila; Syam, Husain (Universitas Negeri Makassar, 2017)
This research is a classroom action research that aims to know the improvement of learn result the subjects of agribusiness of vegetables crops by using Numbered Heads Together (NHT) learning model on class XIc learners of Agronomy of SMK Negeri 2 Soppeng. The subjects of this study were learners of class XIc Agronomy SMK Negeri 2 Soppeng which amounted to 19 people with details of 14 women and 5 men. Data collection technique in this research is using observation sheet, written test, questionnaire and documentation. Data analysis technique in this research is qualitative and quantitative analysis. The results of this study indicate the application of NHT learning model can improve learning outcomes of learners of class XIc Agronomy SMK Negeri 2 Soppeng. It is based on the value of learning outcomes obtained the learners from cycle I to cycle II has increased. Learners learning outcomes in cycle I with an average value of 79.26% with classical mastery of class 84.21%. While the learning outcomes of learners in cycle II with an average value of 94.68% with classical mastery of class is 100%.